Islamic Educational Psychology from Zakiah Daradjat’s Perspective in Addressing Students’ Moral Decline: Psikologi Pendidikan Islam Perspektif Zakiah Daradjat dalam Menghadapi Dekadensi Moral Peserta Didik - Rizky Firnanda; M. Hajar Dewantoro; Fathya Shafa Diani (SiRad: Pelita Wawasan, 2026)
The moral decline of students has become one of the serious challenges in the field of education, characterized by the deterioration of moral values, discipline, responsibility, and social awareness. This phenomenon is influenced by various factors, including technological advancement, social environment, weak character education, and the decreasing internalization of spiritual values within the educational process. In this context, Zakiah Daradjat’s concept of Islamic educational psychology is highly relevant, as it offers an approach that integrates psychological aspects with Islamic values in shaping students’ personalities. This study aims to analyze the concept of Islamic educational psychology according to Zakiah Daradjat and its relevance in addressing students’ moral decline. The research employed a Systematic Literature Review (SLR) method based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework. The research process involved the identification, screening, quality assessment, and synthesis of literature obtained from various relevant academic databases. Literature meeting the inclusion criteria was then qualitatively analyzed to gain a comprehensive understanding of Zakiah Daradjat’s concepts and their implementation in Islamic education. The findings reveal that Zakiah Daradjat emphasizes the importance of balancing physical and spiritual aspects in education, strengthening religious education, fostering mental health, promoting educators’ role modeling, and enhancing the roles of family and environment in students’ character development. The study also demonstrates that the Islamic educational psychology approach developed by Zakiah Daradjat has strong relevance in addressing the challenges of moral decline in the modern era, as it integrates intellectual, emotional, and spiritual dimensions holistically. Therefore, Zakiah Daradjat’s ideas can serve as a conceptual foundation for the development of Islamic education oriented toward character building and the cultivation of noble moral values among students. [Dekadensi moral peserta didik menjadi salah satu permasalahan serius dalam dunia pendidikan yang ditandai dengan menurunnya nilai-nilai akhlak, disiplin, tanggung jawab, dan kepedulian sosial. Fenomena ini dipengaruhi oleh berbagai faktor, seperti perkembangan teknologi, lingkungan sosial, lemahnya pendidikan karakter, serta berkurangnya internalisasi nilai-nilai spiritual dalam proses pendidikan. Dalam konteks tersebut, pemikiran Zakiah Daradjat mengenai psikologi pendidikan Islam menjadi relevan karena menawarkan pendekatan yang mengintegrasikan aspek psikologis dan nilai-nilai keislaman dalam pembentukan kepribadian peserta didik. Penelitian ini bertujuan untuk menganalisis konsep psikologi pendidikan Islam menurut Zakiah Daradjat serta relevansinya dalam menghadapi dekadensi moral peserta didik. Metode penelitian yang digunakan adalah Systematic Literature Review (SLR) dengan mengacu pada tahapan Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Proses penelitian dilakukan melalui identifikasi, penyaringan, evaluasi kualitas, dan sintesis terhadap literatur yang diperoleh dari berbagai basis data akademik yang relevan. Literatur yang memenuhi kriteria inklusi kemudian dianalisis secara kualitatif untuk memperoleh pemahaman yang komprehensif mengenai konsep dan implementasi pemikiran Zakiah Daradjat dalam pendidikan Islam. Hasil penelitian menunjukkan bahwa Zakiah Daradjat menekankan pentingnya keseimbangan antara aspek jasmani dan rohani dalam pendidikan, penguatan pendidikan agama, pembentukan kesehatan mental, keteladanan pendidik, serta peran keluarga dan lingkungan dalam pembinaan karakter peserta didik. Temuan penelitian juga menunjukkan bahwa pendekatan psikologi pendidikan Islam yang dikembangkan Zakiah Daradjat memiliki relevansi yang kuat dalam menghadapi tantangan dekadensi moral di era modern karena mampu mengintegrasikan dimensi intelektual, emosional, dan spiritual secara holistik. Dengan demikian, pemikiran Zakiah Daradjat dapat menjadi landasan konseptual dalam pengembangan pendidikan Islam yang berorientasi pada pembentukan karakter dan akhlak mulia peserta didik]